Together I Can! Joint Attention Boosts 3‐ to 4‐Year‐Olds' Performance in a Verbal False‐Belief Test. Issue 1 (20th April 2018) - Psouni, Elia; Falck, Andreas; Boström, Leni; Persson, Martin; Sidén, Lisa; Wallin, Maria
Abstract : Effects of joint attention were addressed on 3‐ to 4‐year‐olds' performance in a verbal false‐Belief Test (FBT), featuring the experimenter as co‐watcher rather than narrator. In two experiments, children ( N = 183) watched a filmed‐FBT jointly with a test leader, disjointed from a test leader, or alone. Children attending jointly with a test leader were more likely to pass the FBT compared with normative data and to spontaneously recall information indicating false‐belief understanding, suggesting that joint attention strengthens the plausibility of the FBT and renders plot‐critical information more salient. In a third experiment ( N = 59), results were replicated using a typical, image‐based FBT. Overall findings highlight the profound impact of experimenter as social context in verbal FBTs, and link recall of specific story features to false‐belief understanding.